2011
DOI: 10.1210/jc.2011-0274
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Function in the First Twenty Weeks of Pregnancy and Subsequent Fetal and Infant Development: A Prospective Population-Based Cohort Study in China

Abstract: Thyroid dysfunction in the first 20 wk of pregnancy may result in fetal loss and dysplasia and some congenital malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
169
7
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(199 citation statements)
references
References 28 publications
(31 reference statements)
16
169
7
7
Order By: Relevance
“…Multiple studies have reported an association of SCH with an increase in the risk of adverse pregnancy and neonatal outcomes, including pregnancy loss, preterm delivery, gestational diabetes, gestational hypertension, preeclampsia, placental abruption, premature rupture of membranes, intrauterine growth restriction, low birth weight, small for gestational age, low Apgar score, and neonatal death (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Furthermore, high TSH levels in women during pregnancy have been associated with an increased risk of neurocognitive deficits in the offspring (17).…”
mentioning
confidence: 99%
“…Multiple studies have reported an association of SCH with an increase in the risk of adverse pregnancy and neonatal outcomes, including pregnancy loss, preterm delivery, gestational diabetes, gestational hypertension, preeclampsia, placental abruption, premature rupture of membranes, intrauterine growth restriction, low birth weight, small for gestational age, low Apgar score, and neonatal death (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Furthermore, high TSH levels in women during pregnancy have been associated with an increased risk of neurocognitive deficits in the offspring (17).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In 1999, interest in undiagnosed maternal thyroid dysfunction was heightened by studies suggesting an association between subclinical thyroid hypofunction and impaired fetal neuropsychological development. 6,7 In one report, children of women whose serum thyrotropin levels during pregnancy were greater than the 98th percentile had a lower IQ than children of matched controls who had a normal thyrotropin level.…”
mentioning
confidence: 99%
“…Five studies on LBW infants and hyperthyroidism pregnancies were retrieved [10] [13] [18] [19] [20]. A meta-analysis showed an increased risk of LBW infants by 1.3-fold with maternal hyperthyroidism compared with normal pregnancies (OR 1.30; 95% CI 1.11 -1.54; p = 0.002; Figure 2).…”
Section: Low Birth Weight Infants and Hyperthyroidismmentioning
confidence: 99%
“…Over the last 20 years, several studies have investigated the effects of maternal thyroid dysfunction during pregnancy on neonatal birth weight. However, these results remain controversial, as some of the published data on maternal thyroid dysfunction have shown an associated increased risk of LBW [6] [7] [10], whereas other studies have found no association with neonatal birth weight [8] [11] [12] [13] [14].…”
Section: Introductionmentioning
confidence: 99%